Regional heterogeneity of cellular prion protein isoforms in the mouse brain - Beringue, V; Mallinson, G; Kaisar, M; Tayebi, M; Sattar, Z; Jackson, G; Anstee, D; Collinge, J; Hawke, S (Oxford University Press, 2003)
Prion diseases are a group of invariably fatal neurodegenerative disorders that include Creutzfeldt–Jakob disease in humans, scrapie in sheep and goats, and bovine spongiform encephalopathy in cattle. The infectious agent or prion is largely composed of an abnormal isoform (PrPSc) of a host encoded normal cellular protein (PrPc). The conversion of PrPc to PrPSc is a dynamic process and, for reasons that are not clear, the distribution of spongiform change and PrPSc deposition varies among prion strains. An obvious explanation for this would be that the transformation efficiency in any given brain region depends on favourable interactions between conformations of PrPc and the prion strain being propagated within it. However, identification of specific PrPc conformations has until now been hampered by a lack of suitable panels of antibodies that discriminate PrPc subspecies under native conditions. In this study, we show that monoclonal antibodies raised against recombinant human prion protein folded into α or β conformations exhibit striking heterogeneity in their specificity for truncations and glycoforms of mouse brain PrPc. We then show that some of these PrPc isoforms are expressed differentially in certain mouse brain regions. This suggests that variation in the expression of PrPc conformations in different brain regions may dictate the pattern of PrPSc deposition and vacuolation, characteristic for different prion strains.